Analisis Hukum Positif Terhadap Pelaksanaan Mediasi Perkara Perceraian di Pengadilan Agama Kota Surabaya - Mujahid, Mushofi Nahar; Ambarwati, Mega Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Mediation in divorce cases is a mandatory stage regulated in PERMA No. 1 of 2016 with the aim of prioritizing peaceful and deliberative dispute resolution. This study aims to analyze the implementation of mediation in divorce cases at the Surabaya Religious Court from a positive legal perspective. The method used is qualitative research with a normative legal approach, which is based on secondary data from the Case Tracking Information System (SIPP). The results of the study indicate that although mediation has been carried out according to procedure, its success rate is still low. Factors such as the emotional readiness of the parties, the limited number of trained mediators, and the lack of public understanding of the purpose of mediation are the main obstacles. Therefore, it is necessary to increase the capacity of mediators, continuous socialization, and a holistic support system so that mediation can truly function as a means of resolving conflicts that are fair, restorative, and humane in the context of family law in Indonesia.